Personal Files as Part of Documentation of CPSU(b)-CPSU Bodies as Source for History of Prisoners of War and Internees Camps of NKVD-MVD of USSR (on Materials of Kemerovo Region State Archive) - M. A. Orlov (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to affairs of a personal nature, constituting a significant part of the documents of regional and local bodies of the CPSU(b)-CPSU. These documents are considered as one of the groups of sources on the history of camps of Main Directorate for POWs and internees (GUPVI) of the NKVD-MVD of the USSR. In the historiographical review, the author indicates a weak level of scrutiny of the sources on the history of the camps, which are stored in the regional state archives. The reasons for this circumstance are commented. On the material of the State archive of the Kemerovo region main groups of cases of a personal nature are characterized: the files on membership in the party, nomenklatura personal files, other personal files. The author of the article pays attention to the circumstances of the appearance of these files. The species composition of the documents deposited in the cases are analyzed. The nature of the information about the camps GUPVI in these documents is discusses. General and specific features typical to selected groups of cases are identified. The factors are listed that complicate the identification and usage of the files of a personal nature that contain information about the camps GUPVI. Some recommendations are given to enhance wider use of these files, to simplify and expedite their search.